A CIP-based numerical simulation of wave interaction with a fluid-filled membrane submerged breakwater. (15th September 2022) - Zhao, Xizeng; Zhou, Yuwei; Zong, Yiyang; Yang, Zhijian; Luo, Min
Abstract: This study proposes an CIP (Constraint Interpolation Profile) viscous flow model that couples the Finite Element Method for structural deformation, to investigate the wave interaction with a fluid-filled membrane submerged breakwater. A modified ghost-cell immersed boundary method is adopted to achieve an accurate simulation of the fluid-structure interaction. After validation by published experimental data, the model is used to study the interaction between regular waves and a fluid-filled membrane submerged breakwater. The excess internal pressure, vorticity field, elastic modulus and structural responses are analyzed. The results show that, in lower excess internal pressure, the wave reflection, vortex shedding and energy dissipation are more significant. Besides, through the analysis of displacement and velocity distribution, three different vibration modes of the membrane structure are identified at different wave frequencies. Highlights: An FDM-FEM viscous flow model is proposed for wave and membrane breakwater interaction. Internal pressure, vorticity field, elastic modulus and structural responses of a membrane breakwater is investigated. The wave reflection, vortex shedding and energy dissipation are found to be more significant in lower internal pressures. Three different vibration response modes of the membrane structure are found at different wave frequencies.